Calcined solution-based PVP influence on ZnO semiconductor nanopeprints properties - Mohamed Kamari, Halimah; Al-Hada, Naif Mohammed; Saion, Elias; Shaari, Abdul Halim; Talib, Zainal Abidin; Flaifel, Moayad Husein; Ahmed, Abdullah Ahmed Ali (MDPI AG, 2016)
water-based solution of polyvinylpyrrolidone (PVP) at various concentrations and zinc nitrates were used in conjunction with calcination to produce zinc oxide semiconductor nanoparticles. The extent to which the zinc oxide semiconductor nanoparticles had become crystallized was measured using X-ray diffraction (XRD), whilst morphological characteristics were determined using scanning electron microscopy (SEM). Transmission electron microscopy (TEM) supported by XRD results were used to evaluate the average particle size. Fourier transform infrared spectroscopy (FT-IR) was then carried out in order to identify the composition phase, since this suggested that the samples contained metal oxide bands and that all organic compounds had been effectively removed after calcination. A UV-VIS spectrophotometer was used to determine the energy band gap and illustrate optical features. Additionally, photoluminescence (PL) spectra revealed that the intensity of photoluminescence decreased with a decrease in particle size. The obtained results have mainly been inclusive for uses by several semiconductor applications in different fields, such as environmental applications and studies, since an absorption process for energy wavelengths could efficiently occur.